Student post-editing corpora: Collection, annotation and analysis. - LEFER, MARIE-AUDE; BODART, ROMANE (Alfinge, 2025)
In this article, we make a case for the collection of student post-editing corpora, with a view to both informing translator education and expanding the scope of corpus-based translation research. To this end, we present the Post-Edit Me! project and its main outcomes. In particular, we describe the principal features of the postedit.me app, developed to facilitate the processing of student post-edited texts, and we outline the Machine Translation Post-Editing Annotation System (MTPEAS), designed to systematize analysis of edits -- i.e. changes made to raw machine translation output -- and standardize annotation of student post-editing. Finally, we present some first findings from analyses of the Post-Edit Me! corpus.